Estudio comparativo de estrés y ansiedad en estudiantes de una universidad de la región Ica: Comparative study of stress and anxiety in students of a university in the Ica region - Romani Pillpe, Guillermo (2023)
The objective of the present investigation was to determine the differences between stress and anxiety in students of a university in the Ica region. To do this, he responds to the area of ​​knowledge Quality of life, resilience and psychological well-being study. The approach was quantitative: a descriptive methodology, comparative design was obtained. The population consisted of 33 students of professional careers in Psychology and Systems Engineering.who completed the II academic cycle in the Written Communication Workshop course at a private university in the Ica region. The instrument used was a test of anxiety and depression. Regarding the descriptive, no significant differences were observed.